Managing the process of electronic communication in a small legal firm - Dziadkiewicz, Michał; Baskiewicz, Nicoletta (Business Informatics, 2016)
The purpose of this article is to present the issues related to the management process in the electronic communication of a small law firm. In the introduction, the role of information and knowledge in shaping the competitiveness of enterprises is presented. Then the phenomenon of electronic communication as a process of data transmission is shown, which on the one hand determines the competitive position of economic entities including law firms and legal counsellors, and on the other hand, it is the subject of legal regulations. Because the information provided by electronic means shall be subject to the professional secrecy of legal attorneys or solicitors, as the principle of confidentiality applicable to lawyers according to relevant legislation does not exempt these entities from the responsibility in terms of the protection of personal data. Another area raised in the article is to identify actions to protect information transmitted electronically. The last part of the study is to present the results of studies that show the extent to which we use e-mail, free applications such as Dropbox and Google Drive. Moreover the issues of the frequency of password changing and encryption of media as well as attacks on data owned by an office have been discussed. The whole content has been summarized with conclusions
Informatyka Ekonomiczna = Business Informatics, 2016, Nr 1 (39), s. 65-74
Keywords: electronic communication process; electronic document; legal regulations on personal data protection; legal professional privilege; proces komunikacji elektronicznej; dokument elektroniczny; regulacje prawne dotyczące ochrony danych osobowych; tajemnica adwokacka